2013
DOI: 10.1016/j.jadohealth.2012.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Mothers' and High School Girls' Perceptions of Cervical Cancer, Human Papilloma Virus, and the Human Papilloma Virus Vaccine

Abstract: Findings may help in developing school or community-based educational programs for Hispanic families. Such programs should provide information on the HPV vaccine and the link between HPV and cervical cancer, and they should assist mothers and girls in communicating to make informed decisions about the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 22 publications
5
53
1
2
Order By: Relevance
“…Rather, qualitative research suggests that parents found open-ended communication ambiguous, frustrating and worrying, leading them to delay HPV vaccination for their adolescents. 61,71,77,78,98,99 Instead of encouraging shared decision making, mixed messages appeared to lead to a "default" communication style in which neither providers nor parents engaged in the decision-making process. 110 Findings also provide evidence of communication disparities in terms of who receives a provider recommendation for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rather, qualitative research suggests that parents found open-ended communication ambiguous, frustrating and worrying, leading them to delay HPV vaccination for their adolescents. 61,71,77,78,98,99 Instead of encouraging shared decision making, mixed messages appeared to lead to a "default" communication style in which neither providers nor parents engaged in the decision-making process. 110 Findings also provide evidence of communication disparities in terms of who receives a provider recommendation for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…4,[18][19][20]71,74,[76][77][78] However, the extent to which parents communicated about HPV vaccination beyond giving consent varied, with qualitative studies suggesting that parents from racial/ethnic minorities or with lower socioeconomic status were less likely to be engaged by providers and more likely than parents from more socially privileged backgrounds to defer to providers' advice. 19,71,73,74,77 Parents were also more likely to follow providers' advice without question when they received a strong, unambiguous recommendation.…”
Section: Communication Rolesmentioning
confidence: 99%
See 3 more Smart Citations